HUBUNGAN JUMLAH BAKTERI STREPTOCOCCUS MUTANS ATCC 25175 DENGAN INDEKS DMF-T BERDASARKAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS ANDALAS KOTA PADANG - Meiza Nerawati; Nila Kusuma; Eti Yerizel (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Caries is a multifactorial disease that is influenced by saliva and teeth as the host, microorganism, substrate, and time. Children with stunting experiencing saliva gland atrophy which decrease saliva flow, buffer function, immunity component, and its antimicrobial activity which increase the risk of caries. The research was done on children aged 6-12 years old in Puskesmas Andalas, Padang, aims to find out the relationship between the number of bacteria and DMF-T index based on stunting cases. Methods: The research method was observational with the cross-sectional study. Salivary sampling was selected by stratified random sampling for 30 stunting kids and 30 normal ones. Result: The result showed that based on the research, the amount of Streptococcus mutans ATCC 25175 bacteria is higher in children with stunting than the normal ones, but not significant statistically; p=0,659 (p>0,05). DMF-T index is higher in children with stunting than in normal ones. Statistical test analysis resulted in p= 0,004 (p<0,005), which shows the relationship between DMF-T and stunting. Conclusion: This research showed that there is no relationship between the number of Streptococcus mutans ATCC 25175 with DMF-T index based on stunting cases.